A global approach to addressing the policy, research and social challenges of male reproductive health. Issue 1 (21st March 2021) - Barratt, Christopher L R; De Jonge, Christopher J; Anderson, Richard A; Eisenberg, Michael L; Garrido, Nicolás; Rautakallio Hokkanen, Satu; Krausz, Csilla; Kimmins, Sarah; O'Bryan, Moira K; Pacey, Allan A; Tüttelmann, Frank; Veltman, Joris A
Abstract: Male infertility is a global health issue; yet to a large extent, our knowledge of its causes, impact and consequence is largely unknown. Recent data indicate that infertile men have an increased risk of somatic disorders such as cancer and die younger compared to fertile men. Moreover, several studies point to a significant adverse effect on the health of the offspring. From the startling lack of progress in male contraception combined with the paucity of improvements in the diagnosis of male infertility, we conclude there is a crisis in male reproductive health. The Male Reproductive Health Initiative has been organized to directly address these issues (www.eshre.eu/Specialty-groups/Special-Interest-Groups/Andrology/MRHI ). The Working Group will formulate an evidence-based strategic road map outlining the ways forward. This is an open consortium desiring to engage with all stakeholders and governments.